DETERMINANTS OF THE TEACHER’S PERCEPTION OF STUDENTS AT THE PRIMARY AND SECONDARY SCHOOL LEVEL - JAKUBCZAK-CHODŹKO , MAGDALENA (Journal of Vasyl Stefanyk Precarpathian National University, 2019)
Contemporary tasks and imposed requirements in the area of education are focused on improving the efficiency and quality of teaching, including counteracting the disturbing phenomena of the “day of liquid modernity” [1, p. 15–29]. The teacher's person is perceived subjectively, from the perspective of the contractor of professional assumptions. The dynamics of educational processes and progressive civilization changes forces us to meet the emerging expectations of educational policy. The look of many leading educators, among others Jan Władysław Dawid, Zygmunt Mysłakowski, Wincenty Okoń, Maria Grzegorzewska, Czesław Banach for personality traits of the teacher has gone to oblivion to give way to schematic and mass teaching. Increasingly, attention is paid to how? and not who? teaches. Studies in the field of psychology and pedagogy pose a question; What should the teacher be like? Using the following article, in which I will base myself on empirical research, I want to answer a completely different aspect, what kind of teacher would the students want?